GAMBARAN OBESITAS SENTRAL PADA MAHASISWA LAKI-LAKI FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO - Marisa Gita Putri; Ari Udiyono; Mateus Sakundarno Adi; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Obesity is one of the prevalent health issues in modern times. One type of obesity that is harmful to health is central obesity. Central obesity is a result of body fat accumulation in the abdomen ; causing degenerative diseases. The purpose of this study to describe the prevalency central obesity in male students. Thereby, the study uses observational research with cross sectional design conducted in the Faculty of Engineering, University of Diponegoro. The population on this study are male students of the Faculty of Engineering, University of Diponegoro to retrieve a sample of 100 people. The sampling technique is simple random sampling. There were abdominal circumference measurement and anthropometry being collected during the process. Out of the 100 respondents, the study found 44% respondents are with central obesity. The advice given to students is to be able to maintain their diet by not eating greasy foods and increasing physical activity by regular exercise.